The Correlations Between Criminal Motivation, Parental Attitudes, and Expressed Emotion Levels in Juvenile Delinquency - Çetin, Asya; Özyürek, Arzu (Fırat Üniversitesi, 2023)
In this study, the correlations between interpersonal motivations for crime, parental attitudes, and emotional expressions of delinquent and non-delinquent children were examined from the children's point of view. The study group included 10 high school students who were pushed to crime and 10 who were not. The Perceived Parent Attitudes Scale, Abbreviated Expressed Emotions Scale, and Interpersonal Criminal Motivation Scale were used to collect the study data. Nonparametric tests were employed in data analysis. The study findings revealed that juvenile delinquents perceived their parents as more loving, caring and participatory; on the other hand, non-delinquent children perceived their parents as more controlling and democratic. It has been observed that non-delinquent children who perceive their parents as loving, caring and participatory, democratic and encouraging individuality do not experience a lack of emotional support and do not perceive their parents as intrusive. It has been determined that juvenile delinquents who lack emotional support, have problems in ending their negative relationships; juvenile delinquents who perceived their parents as angry increased the feeling of revenge; on the other hand, non-delinquent children who perceive their parents as intrusive, have a higher tendency to maintain negative relationships.

Bu çalışmada, suça sürüklenen ve suça sürüklenmeyen çocukların suça ilişkin kişilerarası motivasyonları, ebeveyn tutumları ve duygu dışavurumları arasındaki ilişki çocukların bakış açısına göre incelenmiştir. Çalışma grubunu 10 suça sürüklenmiş ve 10 suça sürüklenmemiş lise öğrencisi oluşturmuştur. Verilerin toplanmasında Algılanan Anne Baba Tutum Ölçeği, Kısaltılmış Duygu Dışavurum Ölçeği ve Suça İlişkin Kişilerarası Motivasyon Ölçeği kullanılmıştır. Veri analizinde parametrik olmayan testlerden yararlanılmıştır. Sonuç olarak; suça sürüklenen çocukların anne-babalarını daha sevecen, ilgili ve katılımcı olarak algıladıkları; suça sürüklenmemiş çocukların ise anne-babalarını daha denetleyici ve demokratik olarak algıladıkları belirlenmiştir. Ebeveynlerini sevecen, ilgili ve katılımcı, demokratik ve bireyselliği cesaretlendirici olarak algılayan suça sürüklenmemiş çocukların duygusal destek yokluğu yaşamadığı ve ebeveynlerini müdahaleci olarak algılamadıkları görülmüştür. Ebeveynlerini demokratik ve bireyselliği cesaretlendirici olmayan şekilde algılayan suça sürüklenen çocukların ise onların sinirli ve müdahaleci olduğunu algıladıkları görülmüştür. Duygusal destek yokluğu yaşayan suça sürüklenen çocukların olumsuz ilişkilerini sonlandırma konusunda problem yaşadıkları; ebeveynlerini sinirli olarak algılayan suça sürüklenen çocukların intikam duygusunun arttığı; ebeveynlerini müdahaleci olarak algılayan suça sürüklenmemiş çocukların ise olumsuz ilişkilerini sürdürme eğiliminin fazla olduğu ortaya çıkmıştır.
ÇOCUKLARIN SUÇA SÜRÜKLENMESİNDE SUÇA İLİŞKİN MOTİVASYON İLE EBEVEYN TUTUMLARI VE DUYGU DIŞAVURUMLARI İLİŞKİSİ